An Islamic Legal Perspective on Child Custody After Divorce Outside the Religious Court - Miftahul Jannah; Erfandi Erfandi (JURNAL MAHASISWA YUSTISI, 2026)
In Islamic law, child custody (hadhanah) is the responsibility to care for, nuture, and educate a child, especially after a divorce. The main purpose of hadhanah is to ensure the welfare and protection of the child. This study aims to understand the phenomenon of child custody after divorce outside the religius court and the Islamic law perspective on child custody after divorce outside the religious court in Lamasi District, Luwu Regency. This research uses a qualitative method with a case study approach, interviuwing parents who are divorce and religious figures in Lamasi District, Luwu Regency. Data collection techniques include interviews and observation. Data analysis techniques use qualitative data analysis which consists of three main activities: data reduction, data presentation, data drawing or verifying conclusions. The research results show that: (1) The phenomenon of child custody after divorce outside the religious court in Lamasi District, Luwu Regency shows a tendency for case resolution post-divorce to occur outside formal legal institutions, especially the Religious Court. Many divorce couples prefer to setle child custody issues throught mutual agreement without going throught formal legal institutions. (2) The Islamic legal view on child custody (hadhanah) post-divorce outside the Religious Court is that custody remains the right of the mother. Islamic law empasizes the principle of benefit and the child’s best interest as considerations in determining who has the right to custody. Therefore, in cases of custody after divorce outside the Religious Court, if it does not contradict Islamic teachings and does not harm the child, the agreed-upon arrangements between the parents are valid as long as they align with the principles and provisions of Islamic law.